2001
DOI: 10.1073/pnas.211229198
|View full text |Cite
|
Sign up to set email alerts
|

Functional cloning and characterization of a UDP- glucuronic acid decarboxylase: The pathogenic fungus Cryptococcus neoformans elucidates UDP-xylose synthesis

Abstract: UDP-xylose is a sugar donor required for the synthesis of diverse and important glycan structures in animals, plants, fungi, and bacteria. Xylose-containing glycans are particularly abundant in plants and in the polysaccharide capsule that is the major virulence factor of the pathogenic fungus Cryptococcus neoformans. Biosynthesis of UDP-xylose is mediated by UDP-glucuronic acid decarboxylase, which converts UDP-glucuronic acid to UDP-xylose. Although this enzymatic activity was described over 40 years ago it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
124
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(132 citation statements)
references
References 33 publications
6
124
0
2
Order By: Relevance
“…Using serial analysis of gene expression or SAGE, Steen and collaborators 50 showed that C. neoformans cells present in the cerebral spinal fluid of rabbit with cryptococcal meningitis are actively engaged in protein synthesis, protein degradation, stress response, small molecule transport and signaling but none of the genes recently described involved in the capsule biosynthesis pathway [51][52][53] has been identified thus far. It may be that none are triggered in this early machinery and/or that the pathogenesis of cryptococcal meningitis in the rabbit differs from that of disseminated cryptococcosis in the mouse or in humans (one major difference is that rabbits have higher body temperature than both mice or humans).…”
Section: Discussionmentioning
confidence: 99%
“…Using serial analysis of gene expression or SAGE, Steen and collaborators 50 showed that C. neoformans cells present in the cerebral spinal fluid of rabbit with cryptococcal meningitis are actively engaged in protein synthesis, protein degradation, stress response, small molecule transport and signaling but none of the genes recently described involved in the capsule biosynthesis pathway [51][52][53] has been identified thus far. It may be that none are triggered in this early machinery and/or that the pathogenesis of cryptococcal meningitis in the rabbit differs from that of disseminated cryptococcosis in the mouse or in humans (one major difference is that rabbits have higher body temperature than both mice or humans).…”
Section: Discussionmentioning
confidence: 99%
“…In brief, a pET-28a plasmid carrying the decarboxylase (UXS1) cDNA (a kind gift of Dr. Tamara Doering) was used to transform E. coli strain BL21(DE3)pLysS. After induction using isopropyl-␤-D-thiogalactopyranoside, the cells were harvested and lysed as described (24). To generate UDP-xylose, 10 l of soluble bacterial protein extract was incubated overnight with 250 nmol of UDP-glucuronic acid (UDP-GlcA) and 125 nmol of NAD ϩ in Tris-Cl, pH 7.4, buffer in a total volume of 50 l at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…As acceptor, a peptide (DDDSIEGSGGR) corresponding to residues 55-65 of Drosophila syndecan (25) was used, which contains the features of an acidic region and a Ser-Gly sequence found around chondroitin and heparan sulfate attachment sites (31,32), as well as an arginine residue which apparently aids detection by MALDI-TOF mass spectrometry (33). For most experiments, the UDP-Xyl donor was synthesized, without subsequent purification, using recombinant Cryptococcus UDP-GlcA decarboxylase (24).…”
Section: Identification and Analysis Of The Drosophila Oxt Gene Andmentioning
confidence: 99%
“…The aqueous phases were combined and analyzed by HPLC using a Phenosphere-ODS2 column (250 3 4.6 mm; Phenomenex, Torrance, CA) or a Spheresorb-ODS2 column (250 3 4.6 mm; Waters, Milford, MA) eluted at 1 mL min ÿ1 with 0.5 M KH 2 PO 4 (A) for 15 min, followed by a gradient to 80% A and 20% methanol over 14 min at a flow rate of 0.7 mL min ÿ1 . Peaks eluted from the ODS2 column were injected onto a Phenosphere-SAX ion exchange column (250 3 4.6 mm; Phenomenex) and eluted at 1 mL min ÿ1 with a linear 2-to 600-mM ammonium-formate gradient formed over 25 min (Bar-Peled et al, 2001). Nucleotides and nucleotide-sugars were detected by UV absorbance using a Waters photodiode array detector.…”
Section: Enzyme Assaysmentioning
confidence: 99%